DAMPAK SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU TERHADAP ADOPSI TEKNOLOGI, PRODUKTIVITAS DAN PENDAPATAN USAHATANI PADI - Herman Supriadi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACTImpact  of Farmer Field School - Integrated Crop Management (FFS-ICM) to the Level Adoption, Productivity and Income of Farmers. Impact study of Farmer Field School - Integrated Crop Management (FFS-ICM) to the level adoption, productivity and income of farmers has been done during 2012 in three districts, namely Subang (West Java), Madiun (East Java), and East Ogan Komering Ulu (OKU) in South Sumatra. This study aims to analyze level of PTT technology adoption, and the impact of SL-PTT to the productivity and income of farmers. The method of analysis used is a comparative analysis of two independent samples using T test statistics, partial budget analysis, and farm cost efficiency. The findings showed that SL-PTT activity resulted in increased rice productivity of 0.40 - 0.60 t/ha or (7.1 - 9.4)% for inbred rice and 0.4 - 1.1 t/ha or (8.0 - 15.7)% for hybrid rice. Based on statistical tests, seed inputs support system (BLBU) in the FFS-ICM activity was not statistically significant effect on increasing rice productivity inbred but significantly increased productivity of hybrid rice. Increasing farmers income by FFS-ICM ranges Rp (0.90 to 1.775) million/ha for inbred rice, and Rp2.04 million/ha for hybrid rice. Package of technology alternative has been widely adopted by farmers, but the basic technology package, especially fertilizer as plant needed, optimum population and pest control systems using IPM approach have not been fully implemented by farmers. Opportunity to increase rice production can be reached through development of VUB, hybrid rice, and direct seeded rice. Threat that must be anticipated is centralized policies and poor coordination of relevant agencies, and the limited extension. Indicatif program that needs to be done next are: a) Developing cooperative inputs / capital access assistance, b) Evaluating the feasibility of the technology, c) Increasing the number of trainers and quality education materials, and d).Functioning of local seed producer. Key words: SL-PTT, impact productivity, income and irrigated lowland rice ABSTRAK Kajian dampak Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) terhadap tingkat adopsi, produktivitas dan pendapatan usahatani padi dilakukan tahun 2012 di tiga kabupaten yaitu Subang (Jawa Barat), Madiun (Jawa Timur), dan Ogan Komering Ulu (OKU) Timur di Sumatera Selatan. Kajian bertujuan menganalisis tingkat adopsi teknologi PTT, dan dampak kegiatan SL-PTT terhadap peningkatan produktivitas dan pendapatan petani. Metode analisis yang dipakai adalah analisis komparatif dua sampel bebas menggunakan uji T statistik, analisis biaya dan pendapatan usahatani, dan efisiensi usahatani. Hasil kajian menunjukkan bahwa kegiatan SL-PTT berdampak terhadap peningkatan produktivitas padi sebesar 0,40 – 0,60 t/ha atau (7,1 – 9,4)% untuk padi inbrida dan 0,4 s/d 1,1 t/ha atau (8,0 - 15,7)% untuk padi hibrida. Berdasarkan uji statistik sistem bantuan saprodi dan benih (BLBU) dalam kegiatan SL-PTT tidak nyata terhadap peningkatan produktivitas padi inbrida tetapi nyata meningkatkan produktivitas padi hibrida. Peningkatan pendapatan petani dengan SL-PTT berkisar Rp (0,90 – 1,775) juta/ha untuk padi inbrida, dan Rp2,04 juta/ha untuk padi hibrida. Paket teknologi pilihan sudah banyak diadopsi petani, tetapi paket teknologi dasar terutama pemupukan sesuai kebutuhan, populasi optimum dan pengendalian OPT sistem PHT belum sepenuhnya diterapkan petani. Peluang peningkatan produktivitas padi dapat melalui pengembangan VUB, padi hibrida dan sistem tanam benih langsung. Ancaman yang harus diantisipasi adalah kebijakan sentralistik dan buruknya koordinasi instansi terkait, dan terbatasnya penyuluh pendamping. Program indikatif yang perlu dilakukan kedepan adalah: a) Mengembangkan koperasi saprodi dan akses modal, b) Evaluasi kelayakan teknologi, c) Meningkatkan jumlah penyuluh dan mutu materi penyuluhan, dan d) Memfungsikan penangkar benih lokal. Kata kunci: SL-PTT, dampak adopsi teknologi, produktivitas, pendapatan,.padi sawah irigasi